2014
DOI: 10.1097/qai.0000000000000142
|View full text |Cite
|
Sign up to set email alerts
|

HIV Outcomes in Hepatitis B Virus Coinfected Individuals on HAART

Abstract: Background Understanding the impact of hepatitis B virus (HBV) coinfection on HIV outcomes in the HAART era continues to be a critical priority given the high prevalence of coinfection and the potential for impaired immunologic, virologic and clinical recovery. Methods Participants from the U.S. Military HIV Natural History Study with an HIV diagnosis, on HAART and serologically confirmed HBV infection status at HAART initiation (HI) were classified into four HBV infection (HB) groups. HIV virologic, immunol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 29 publications
4
49
1
1
Order By: Relevance
“…Moreover, in co-infected patients, exertion of gp 120 on elevations and intracellular accumulation of HBV, DNA as well as HBsAg is proposed (Figure 1) to cause hepatotoxicity. In a clinical study, association of HBV and HIV co-infection with higher levels of HBV DNA has suggested that factors other than a direct virusvirus interaction might contribute to the increased HBV DNA levels [9] . While it has been shown that the HBV-X protein acts in alliance with HIV-tat in facilitating HIV replication [44] , the synergistic effect of tat, if any, on HBV life cycle is not known.…”
Section: Underlying Mechanismsmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, in co-infected patients, exertion of gp 120 on elevations and intracellular accumulation of HBV, DNA as well as HBsAg is proposed (Figure 1) to cause hepatotoxicity. In a clinical study, association of HBV and HIV co-infection with higher levels of HBV DNA has suggested that factors other than a direct virusvirus interaction might contribute to the increased HBV DNA levels [9] . While it has been shown that the HBV-X protein acts in alliance with HIV-tat in facilitating HIV replication [44] , the synergistic effect of tat, if any, on HBV life cycle is not known.…”
Section: Underlying Mechanismsmentioning
confidence: 99%
“…Furthermore, in co-infection cases, HIV severely alters the natural history of hepatitis B [3,24] . HIV co-infection significantly decreases the rate of hepatitis B e antigen (HBeAg) clearance up to five-fold and increases the level of HBV replication [9,25] . Even co-infected persons who seroconvert to protective antibody to hepatitis B surface antigen (HBsAg) [anti-hepatitis B surface antibody (HBsAb)], remain at risk of reverse-seroconversion, and subsequent reactivation of HBV [26,27] .…”
Section: Pathogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…HIV infection adversely impacts on the progression of liver diseases. For example, HIV/hepatitis B virus (HBV) co-infected patients had significantly decreased rate of hepatitis B surface antigen (HBsAg) clearance and increased HBV replication than HBV monoinfected individuals (2)(3), and HIV/hepatitis C virus (HCV) coinfected patients had lower rate of HCV viral suppression than HCV monoinfected controls (4). Consequently, progression to cirrhosis is more rapid in HIV-infected patients with chronic liver diseases (5)(6).…”
Section: Introductionmentioning
confidence: 99%